Le Fonds monétaire international, la réforme monétaire et le Tiers-Monde - Cameron, Duncan (L'Actualité économique, 1979)
A second series of amendments to the Bretton Woods charter has recently been approved by the IMF Board of Directors. This article provides a commentary on the negotiations leading up to this reform and attaches particular importance to those aspects which concern the Third World. The article analyzes the nature of the IMF and the role that it has played within the international community, before examining the reform proposals and the failure to satisfy the limited aspirations of the Third World countries. The principal topics considered include: the link between development finance and international monetary reform, the propositions studied by the Committee of Twenty, and the decisions taken by the Interim Committee at Jamaica in 1976.